Stability and ultimate boundedness of solutions to Certain third-order differential equations (2010)
We employ Lyapunov’s second method to investigate uniform asymptotic stability, ultimate boundedness and uniform ultimate boundedness of solutions to certain third-order non-linear differential equations. Our results improve some well-known results in the literature.